Microbiota characterization in Blastocystis-colonized and Blastocystis-free school-age children from Colombia (2020)
Background Blastocystis is a protist that lives in the intestinal tract of a variety of hosts, including humans. It is still unclear how Blastocystis causes disease, which presents an ongoing challenge for researchers. Despite the controversial findings on the association between Blastocystis and clinical digestive manifestations, there is currently no consensus as to whether this protozoan actually behaves as a pathogen in humans. Furthermore, the relationship between Blastocystis and the intestinal microbiota composition is not yet clear. For that reason, the aim of this study was to identify if colonization by Blastocystis is related to changes in the diversity and relative abundance of bacterial communities, compared with those of Blastocystis-free individuals in a group of Colombian children. Methods We took stool samples from 57 school-aged children attending a daycare institution in Popayán (Southwest Colombia). Whole DNA was extracted and examined by 16S-rRNA amplicon-based sequencing. Blastocystis was detected by real time PCR and other intestinal parasites were detected by microscopy. We evaluated if Blastocystis was associated with host variables and the diversity and abundance of microbial communities. Results The composition of the intestinal bacterial community was not significantly different between Blastocystis-free and Blastocystis-colonized children. Despite this, we observed a higher microbial richness in the intestines of children colonized by Blastocystis, which could, therefore, be considered a benefit to intestinal health. The phylum Firmicutes was the predominant taxonomic unit in both groups analyzed. In Blastocystis-free individuals, there was a higher proportion of Bacteroidetes; similarly, in children colonized by Blastocystis, there was a higher relative abundance of the phylum Proteobacteria; however, no statistically significant differences were found between the comparison groups. Conclusions The presence of Blastocystis showed a decrease in Bacteroides, and an increase in the relative abundance of the genus Faecalibacterium. It was also evident that the presence of Blastocystis was unrelated to dysbiosis at the intestinal level; on the contrary, its presence did not show statistically differences in the intestinal microbiota composition. Nevertheless, we believe that Blastocystis plays a role in the ecology of the intestinal microbiota through its interaction with other microbial components.